2016
DOI: 10.5958/2231-5691.2016.00024.1
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant, Analgesic Activity and SAR Studies of Substituted Benzimidazoles

Abstract: ABSTRACT:Purpose. Benzimidazole class of compound is found to have diverse biological properties. From the literature study, it is observed that depression is a severe mental disease affecting a huge population and pain is affecting about 20% of world population. In continuation of our previous research work, we selected benzimidazole pharmacophore to further explore its pharmacological activities. Methods. Forced swim test and Thermal stimulus test were used to assess the antidepressant and analgesic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
(16 reference statements)
0
17
0
Order By: Relevance
“…2-Substituted benzothiazoles have attracted considerable interest due to their diverse biological and pharmaceutical properties, such as antiulcer and antihelminthic [14], antihypertensive [15], anticoagulant [16], antiallergic [17], analgesic [18], anti-inflammatory [19], antimicrobial [20], antivirial [21], antiparasitic [22], anticancer [23] and enzyme inhibitory activity [24]. The increasing applications of metal complexes of 2-substituted benzothiazoles, capable of forming multifunctional complexes, in the area of optoelectronics, the synthesis of fluorogenic enzyme substrates and fluorescent materials are also well recognized [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…2-Substituted benzothiazoles have attracted considerable interest due to their diverse biological and pharmaceutical properties, such as antiulcer and antihelminthic [14], antihypertensive [15], anticoagulant [16], antiallergic [17], analgesic [18], anti-inflammatory [19], antimicrobial [20], antivirial [21], antiparasitic [22], anticancer [23] and enzyme inhibitory activity [24]. The increasing applications of metal complexes of 2-substituted benzothiazoles, capable of forming multifunctional complexes, in the area of optoelectronics, the synthesis of fluorogenic enzyme substrates and fluorescent materials are also well recognized [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5], antiviral (anti-HIV, anti-HBV and HCV (Hepatitis B and C, etc.) [6,7], antiulcer [8,9] antiinflammatory/analgesic [10,11], antihistaminic (antiallergic) [12,13], antagonist [14], antitubercular [15], antidepressant [16], antidiabetic [17], antihypertensive [18], antioxidant [19][20][21][22] and antitumor/anticancer [23,24], have been synthesized. Also, some benzimidazole derivatives have some optical applications such as photoluminescents [25], whitening agents [26] and dye laser [27].…”
Section: Introductionmentioning
confidence: 99%
“…Structure-activity relationship (SAR) studies have shown that 1,2,5,6-substituted benzimidazoles with various substituents are analgesic and antiinflammatory agents [22]. Also, SAR studies were accomplished for antiviral, anticancer, antihelminthic, antimicrobial, antimycobacterial, antidiabetic, antiprotozoal, antipsychotic, antidepressant, and antioxidant benzimidazole derivatives [1,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%